Structural, magnetic, thermal, mesomorphic and density functional theoretical studies of complexes of copper(II) and iron(II) with carboxylate ions and 2,2’-bipyridine ligands / Lailatun Nazirah Ozair - Lailatun Nazirah, Ozair (2016)
This research is focused on the syntheses and characterization of magnetic, thermally stable and mesomorphic complexes of copper(II) and iron(II) of general formula [Cu2(RCOO)4(bpy)2] and [Fe(RCOO)2(bpy)] (R = CH3(CH2)6-14, p-CH3(CH2)9-15C6H4; bpy = 2,2’-bipyridine), respectively, and study their magnetic properties (for the copper(II) complexes) and structures (for the iron(II) complexes) by density functional theories (DFT). The structures of ligands and complexes were deduced by CHN elemental analyses, 1 H-NMR spectroscopy (for ligands), FTIR spectroscopy, UV-vis spectroscopy, and X-ray crystallography (for single crystals). The magnetic susceptibilities of complexes were determined at room temperature by the Gouy method, their thermal stabilities by thermogravimetry (TG), and their mesomorphic properties by differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). The geometry optimization and frequencies calculations were done using Gaussian09W package with DFT B3LYP method and 6-31G basis set. A total of nine copper(II) complexes and eight iron(II) complexes were successfully synthesised and characterised. All copper(II) complexes have square pyramidal Cu(II) centres with monodentate and syn-anti bridging carboxylato ligands, were magnetic, thermally stable (Tdec ranged from 173 o C to 272 o C), and mesomorphic. All iron(II) complexes were octahedral with a mixture of high spin (HS) and low spin (LS) iron(II) atoms at room temperature, and thermally stable (Tdec ranged from 152 o C to 160 o C). The alkylcarboxylate complexes, except for [Fe2(CH3(CH2)10COO)4(bpy)], were not mesomorphic,. The arylcarboxylate complexes were mesomorphic. The molecular modelling for copper(II) complex (1) and iron(II) complexes (6 and 16) showed good agreement between the experimental and theoretical data.